Valoración química de leche en bovinos suplementados con panca de arroz amonificada con urea en la finca la Delia del Cantón Baba - Quinga Cedeño, Edith Malena (2020)
VII. SUMARY The present investigation was carried out in the “La Delia cattle ranch” between (insert the months and year). The chemical quality of the milk was evaluated in bovines supplemented with rice pan ammoniated with four percent urea. For the study, 3 cows were used, bottle with preservative (Bronopol (2-bromo-2-nitropropane-1,3 diol). The treatments were composed of: treatment one Free grazing (control), treatment two rice husks treated with urea (5 kg / cow / day) and treatment three, untreated rice pan (5 kg / cow / day) The design used was a 3x3 Latin square, with 3 treatments and 3 repetitions. For the evaluation and comparison of measures of the treatments, the Tukey test will be performed at 5% significance. the results were subjected to the analysis of variance in the statistical program Sisvar. The average percentage of fat was; week 1 (2.9%), week 2 (3.9%) and week 3 (5.8%), for protein the values were: in week 1 it was (3.9%), in week 2 (4.3%) and week it was 3 (4.2%), in the total solids parameters the following values were obtained: week 1 (11.5%), week 2 (13.94%) and week 3 (12.7%). There is an increase in the fat parameter in raw milk, in cows fed with the ammonified panca and dry panca treatment in relation to the animals subjected to free grazing: week 1 (2.9%), week 2 (3.9%), week 3 (5.86 %). Regarding protein, it is concluded that there is an increase from 1.04 to 1.46 in the percentage of protein in raw milk associated with the food provided in each treatment.